2009 IEEE LEOS Annual Meeting Conference Proceedings 2009
DOI: 10.1109/leos.2009.5343470
|View full text |Cite
|
Sign up to set email alerts
|

Wafer-level hermetic vacuum micro-packaging technology for IR detector applications

Abstract: A low-cost low temperature wafer-level vacuum micropackage has been developed exhibiting an equivalent flow rate of 3.8x10 -14 Torr.L/sec for storage at 80 °C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…1). (4,5) and is defined by the geometrical bolometer leg design, with the leg area A, the leg length l and the material specific thermal conductivity k of the different material layers.…”
Section: Physical Bolometer Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…1). (4,5) and is defined by the geometrical bolometer leg design, with the leg area A, the leg length l and the material specific thermal conductivity k of the different material layers.…”
Section: Physical Bolometer Modelmentioning
confidence: 99%
“…Independently from which packaging and bonding process is chosen, the increasing internal pressure directly leads to performance reductions of the IRFPA. The influence of changing pressure on the imager performance was also investigated in [2][3][4]. For that reason it is necessary to measure and track the internal pressure level of the package to investigate and assure the quality and reliability of the IRFPA.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the vacuum packaging, our substrate-free FPA is unlike other optical or IR MEMS devices [5], [6], [9], [10]. There are two transparent windows with different materials for visible and IR light, respectively, that need to be assembled with a metal chamber.…”
Section: Packaging and Measurementmentioning
confidence: 99%
“…They demonstrated that, when the internal pressure is 10 −2 torr or below, the thermal conductance by the gas inside the vacuum package is much smaller than the thermal conductance of the solid part of the bolometer [3]. Other works such as [4]- [6] were also focused on the relationship between the vacuum and sensitivity of the bolometer, indicating that low air pressure in the package contributes to the sensitivity. The relationship between response time and air pressure, however, has not been mentioned yet.…”
Section: Introductionmentioning
confidence: 99%